2018
DOI: 10.1111/desc.12680
|View full text |Cite
|
Sign up to set email alerts
|

Neural signatures of co‐occurring reading and mathematical difficulties

Abstract: Impaired abilities in multiple domains is common in children with learning difficulties. Co-occurrence of low reading and mathematical abilities (LRLM) appears in almost every second child with learning difficulties. However, little is known regarding the neural bases of this combination. Leveraging a unique and tightly controlled sample including children with LRLM, isolated low reading ability (LR), and isolated low mathematical ability (LM), we uncover a distinct neural signature in children with co-occurri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 63 publications
0
20
0
Order By: Relevance
“…datasets adding up to n = 2,628 individuals (n = 735 individuals with MLD, n = 1,893 TD individuals). The studies of Price et al (2007), Skeide et al (2018), and…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…datasets adding up to n = 2,628 individuals (n = 735 individuals with MLD, n = 1,893 TD individuals). The studies of Price et al (2007), Skeide et al (2018), and…”
Section: Resultsmentioning
confidence: 99%
“…The analysis was repeated after removing the largest study representing 72.03% of participants (Study 2, n = 1899) and no evidence of a difference was similarly found (OR = 1.60, 95% confidence interval (CI) = .95, 2.69, Z = 1.77, p = .08). We refrain from interpreting the last p-value as weak evidence for a difference, as three studies showing no differences but reporting zero left-handers for both groups were not included in the analysis, as mentioned above (McCaskey, 2018b;Price et al, 2007;Skeide et al, 2018). Egger's t provided evidence for small study bias, t(11), = 3.13, p = .010.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations